A new ursane triterpenoic acid and other potential anti-inflammatory and anti-arthritic constituents from EtOAc extracts of Vitellaria paradoxa stem bark. (4th November 2015) - Eyong, Kenneth Oben; Foyet, Harquin Simplice; Baïrys, Guerisson; Ngosong Folefoc, Gabriel; Acha Asongalem, Emanuel; Lagojda, Andreas; Lamshöft, Marc
Abstract: Objective: Vitellaria paradoxa (shea tree) is used in traditional medicine for the treatment of various ailments, including, inflammation and fever. Therefore the present research investigates the anti-inflammatory and anti-rheumatic effects of V. paradoxa stem bark extracts in rats and the isolation and characterization of its active constituents. Methods: The anti-inflammatory activity of ethyl acetate extract of V. Paradoxa (VPEE) was evaluated by use of the carrageenan-induced paw oedema model in rats. Moreover, rheumatoid arthritis (RA) was induced by injection of Freund's Completed Adjuvant (FCA) into the subplantar surface of the hind paw of the male Wistar rats. Paw volume was measured plethysmometrically. Joint swelling was measured using electronic vernier caliper. Hot plate test was used to assess the effect of VPEE on hyperalgesia while open field was used to assess the locomotors activity. The relative weight of spleen, liver and thymus was obtained as well as some haematological parameters. Tibiotarsal joint was extracted for histopathology under light microscope. Chemical analysis was carried out by high resolution mass spectrometry and one and two-dimensional NMR techniques. Results: LC–MS analysis of the EtOAc extract revealed the presence of a new triterpenoid and several known compounds. The structure of the novel compound was elucidated by means of LC–MS and selected 1D and 2D-NMR experiments. The biological effects of ethyl acetate (VPEE), methanol (VPME) and water extracts (VPAE) of V . paradoxa were tested on carrageenan model of acute inflammation and FCA-induced rheumatoid arthritis animal model. In the carrageenan-induced inflammation, VPEE (150 mg/kg) significant (66.67%) inhibited the first (after 1 h) and the second phase (4–6 h) of edema formation. On the Complete Freund's adjuvant-induced rheumatoid arthritis, VPEE at the same dose showed a significantly protective effect. On days 19–28th of treatment, the maximum inflammatory percentage was between 9.60 and 8.91% for the VPEE compared to 30.91–24.29% for the controls. All the extracts significantly reduced the score of arthritis but the maximal reduction was obtained with the VPEE on day 24th of the experimentation. The altered haematological parameters in the arthritic rats were significantly recovered to near normal by the treatment with VPEE at the dose of 150 mg/kg. Further histological studies revealed the anti-arthritic activity by preventing cartilage destruction of the arthritic joints of adjuvant arthritic rats. The spleen hypertrophy induced by the FCA was also significantly inhibited. Conclusion: These findings provide pharmacological basis for the application of the VPEE in inflammatory disorders. Graphical abstract: